Juxtaposed concessive constructions: a usage-based functional analysis - Ivo Costa do Rosário (Acta Scientiarum. Language and Culture, 2015)
This paper presents a theoretical and empirical discussion about juxtaposed concessive clauses. It proposes an interpretation of distinct constructional patterns outside the prototypical scheme of finite and nonfinite concessive clauses. Based on a written language corpus, by means of the theoretical assumptions of the Usage-Based Functional Linguistics, it is assumed that concessive juxtaposed clauses have special characteristics that distinguish them from the prototypical concessive ones.